(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Investing in tourism contributes to providing more job opportunities, enhancing competitiveness in the tourism sector, and increasing the country’s income and general public revenues to achieve economic growth in the country.